The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1081/ada-100101846
|View full text |Cite
|
Sign up to set email alerts
|

The Autonomy of Mood Disorders Among Cocaine-Using Methadone Patients

Abstract: This study uses an algorithm to determine whether patients dually diagnosed with a mood disorder and cocaine dependence have either (a) an autonomous mood disorder (onset of mood disorder prior to substance use disorder (SUD) or mood disorder symptoms persist during periods of abstinence or (b) a nonautonomous mood disorder (onset of SUD preceded mood disorder and mood disorder symptoms remit during periods of abstinence). The relationship among autonomy, patient characteristics, and treatment completion is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A systematic review found most studies showed no significant relationship between age and attrition; however, most studies reporting significant associations indicate younger age as a risk factor for attrition (Brorson et al, 2013;Stark, 1992;Wickizer et al, 1994). Regarding race/ethnicity, some studies find minorities are less likely to complete treatment than non-Hispanic Whites (Guerrero, Marsh, Duan, Perron, & Lee, 2013; U.S. Department of Health and Human Services (USDHHS), Substance Abuse and Mental Health Services Administration (SAMHSA), Center for Behavioral Health Statistics and Quality, 2017b), others find the opposite (Rosenblum et al, 1999;Stack, Cortina, Samples, Zapata, & Arcand, 2000), and some find no difference in completion rates across racial/ethnic groups (Stark, 1992). In contrast, multiple studies consistently identify lower education as a risk factor for attrition (Brorson et al, 2013;Hillhouse, Marinelli-Casey, Gonzales, Ang, & Rawson, 2007…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…A systematic review found most studies showed no significant relationship between age and attrition; however, most studies reporting significant associations indicate younger age as a risk factor for attrition (Brorson et al, 2013;Stark, 1992;Wickizer et al, 1994). Regarding race/ethnicity, some studies find minorities are less likely to complete treatment than non-Hispanic Whites (Guerrero, Marsh, Duan, Perron, & Lee, 2013; U.S. Department of Health and Human Services (USDHHS), Substance Abuse and Mental Health Services Administration (SAMHSA), Center for Behavioral Health Statistics and Quality, 2017b), others find the opposite (Rosenblum et al, 1999;Stack, Cortina, Samples, Zapata, & Arcand, 2000), and some find no difference in completion rates across racial/ethnic groups (Stark, 1992). In contrast, multiple studies consistently identify lower education as a risk factor for attrition (Brorson et al, 2013;Hillhouse, Marinelli-Casey, Gonzales, Ang, & Rawson, 2007…”
Section: Demographic Characteristicsmentioning
confidence: 99%